The Redemptive Burdens of History and Qualitative Education in Nigeria’s Nation Building - Lucky Nziadam (International Journal on Integrated Education, 2022)
This work discussed the redemptive burden of history and qualitative education in the process of Nigeria’s nation-building. The paper advocates for the return of history into the primary and secondary schools in Nigeria. In furtherance of this revered enthusiasm, the paper argues for a compulsory but genuine teaching of the history of the country which should be pursued as a matter of policy by the ministries of education, information and culture and their parastatals. This is necessary to preserve the cultural and intellectual repositories of the country for posterity. As a philosophical paper, the analytical methods were employed with the clarification of some key words. Based on that, some recommendations such as the promotion of history in the schools were made. As a complement, the state government with private sectors initiative should take the ambitious step of setting up mini-museum of history in different local government headquarters, as practiced in more enlightened societies. This will also facilitate education tours and present an ingenious way of being acquainted with history. From the study of history and education some basic virtues such as justice, equality, brotherliness, brother- keeper was recommended for a more stable nation.